Appropriateness of pancreatic resection in high‐risk individuals for familial pancreatic ductal adenocarcinoma: a patient‐level meta‐analysis and proposition of the Beaujon score. Issue 3 (1st April 2019) - de Mestier, Louis; Muller, Marie; Cros, Jérôme; Vullierme, Marie-Pierre; Vernerey, Dewi; Maire, Frédérique; Dokmak, Safi; Rebours, Vinciane; Sauvanet, Alain; Lévy, Philippe; Hammel, Pascal
Abstract : Background: About 5% of pancreatic ductal adenocarcinomas are inherited due to a deleterious germline mutation detected in 20% or fewer families. Pancreatic screening in high‐risk individuals is proposed to allow early surgical treatment of (pre)malignant lesions. The outcomes of pancreatic surgery in high‐risk individuals have never been correctly explored. Objectives: To evaluate surgical appropriateness and search for associated factors in high‐risk individuals. Methods: A patient‐level meta‐analysis was performed including studies published since 1999. Individual classification distinguished the highest risk imaging abnormality into low‐risk or high‐risk abnormality, and the highest pathological degree of malignancy of lesions into no/low malignant potential or potentially/frankly malignant. Surgical appropriateness was considered when potentially/frankly malignant lesions were resected. Results: Thirteen out of 24 studies were selected, which reported 90 high‐risk individuals operated on. Low‐risk/high‐risk abnormalities were preoperatively detected in 46.7%/53.3% of operated high‐risk individuals, respectively. Surgical appropriateness was consistent in 38 (42.2%) high‐risk individuals, including 20 pancreatic ductal adenocarcinomas (22.2%). Identification of high‐risk abnormalities was strongly associated with surgical appropriateness at multivariate analysis ( P = 0.001). We proposed a score and nomogram predictive of surgical appropriateness, including high‐risk abnormalities, age and existence of deleterious germline mutation. Conclusion: Overall, 42.2% of high‐risk individuals underwent appropriate surgery. The proposed score might help selecting the best candidates among high‐risk individuals for pancreatic resection.